2017
DOI: 10.7554/elife.28685
|View full text |Cite
|
Sign up to set email alerts
|

Defective synaptic transmission causes disease signs in a mouse model of juvenile neuronal ceroid lipofuscinosis

Abstract: Juvenile neuronal ceroid lipofuscinosis (JNCL or Batten disease) caused by mutations in the CLN3 gene is the most prevalent inherited neurodegenerative disease in childhood resulting in widespread central nervous system dysfunction and premature death. The consequences of CLN3 mutation on the progression of the disease, on neuronal transmission, and on central nervous network dysfunction are poorly understood. We used Cln3 knockout (Cln3Δex1-6) mice and found increased anxiety-related behavior and impaired ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 89 publications
3
30
0
Order By: Relevance
“…14 months) (Grunewald et al . ). Based on heightened Ca 2+ responses to glutamate, Cln3 Δex7/8 neurons were expected to exhibit metabolic deficits.…”
Section: Discussionmentioning
confidence: 97%
“…14 months) (Grunewald et al . ). Based on heightened Ca 2+ responses to glutamate, Cln3 Δex7/8 neurons were expected to exhibit metabolic deficits.…”
Section: Discussionmentioning
confidence: 97%
“…The authors proposed that CTSD is therefore an important regulator of synaptic vesicle recycling, and that its deficiency blocks this process causing neuronal dysfunction and the epilepsy prone behavior in NCL10. In another juvenile mouse model of NCL (Cln3 ∆ex1-6 ), the authors reported specific synaptic neurotransmission deficits in multiple brain areas correlating with anxiety and memory impairments [125]. Whole cell patch clamp recordings from principal neurons (PNs) in the basolateral amygdala (BLA) displayed reduced frequency of mIPSCs (miniature inhibitory postsynaptic currents) and sIPSCs (spontaneous inhibitory postsynaptic currents) as well as reduction of peak amplitude in evoked GABAergic IPSCs.…”
Section: Functional Synaptic Defectsmentioning
confidence: 99%
“…Our findings reinforced the therapeutic value of NtBuHA in INCL. However, some recent findings argued against AMPAR changes in Batten disease and ascribed its synaptopathy to presynaptic changes, not aberrant levels of AMPARs 46,47. Thus, further investigations are required.…”
mentioning
confidence: 99%